EVALUATION OF ACCESSIBILITY TO HEALTH FACILITIES PROBLEMATIQUE VIA SPACE SYNTAX METHOD IN THE CONTEXT OF TURKIYE LEGISLATION - Öztürk, Sevgi; Yılmaz, Dilara; Işınkaralar, Öznur (Journal of Economics and Administrative Sciences, Giresun University, 2025)
The regulation on the Preparation of Spatial Plans guides health infrastructure planning at the zoning scale, including provisions for minimum per capita land requirements in Türkiye. However, at the local level, the spatial distribution and accessibility of health facilities play a critical role in ensuring equitable and efficient healthcare service delivery. This study aims to evaluate the adequacy of health facility areas at the neighborhood scale in the Central District of Kastamonu Province. First, the health facility area per capita was calculated for each neighborhood to assess compliance with the legal standards. Subsequently, spatial intelligibility was analyzed using DepthMapX-0.29 software by generating connectivity and integration maps and calculating their correlation coefficient (R²). The findings reveal that while the Saraçlar neighborhood had the highest intelligibility value (R² = 0.48), it was found to be insufficient regarding the allocated health facility area. These findings indicate that although the area is perceptually accessible, there is a spatial deficiency in healthcare provision. Ensuring access to health services is a fundamental human right, and from this perspective, transportation and spatial planning must prioritize enhancing access to public services. The results underline the necessity of revising spatial planning regulations by incorporating perceptual accessibility considerations to address local healthcare needs better.